STRIAE DISTENSAE: A LITERATURE REVIEW OF TREATMENT MODALITIES AND THEIR CLINICAL EFFICACY - Sylwia Boczek,; Mikołaj Herba,; Kacper Ordon,; Patrycja Misiaszek, (International Journal of Innovative Technologies in Social Science, 2025)
Background. Striae distensae, or stretch marks, are common linear dermal scars resulting from collagen and elastin disruption. They frequently affect women during puberty and pregnancy, as well as individuals experiencing rapid weight gain or endocrine disorders, and can substantially impair quality of life.Aim. This review aimed to synthesize current literature on the pathophysiology, risk factors, and therapeutic options for striae distensae, with a focus on aesthetic medicine techniques such as laser therapies and microneedling.Materials and Methods. Between March and June 2025, PubMed, PMC, and Google Scholar were systematically searched using the keywords “aesthetic medicine,” “striae,” “stretch marks,” “laser therapy,” and “microneedling.” Studies reporting clinical efficacy, histological changes, and safety profiles were included.Results. Topical agents (e.g., retinoids, Centella asiatica, and hyaluronic acid) produced modest improvements. Among aesthetic procedures, chemical peels, platelet rich plasma, microdermabrasion, carboxytherapy, and radiofrequency demonstrated variable success. Microneedling and fractional CO₂ laser treatments yielded the most pronounced results, especially in combination, achieving up to 60-70% improvement in early (striae rubrae) lesions. However, mature hypopigmented striae albae remained particularly resistant, with improvements typically below 30%. Adverse events-primarily transient erythema and post inflammatory hyperpigmentation-were more common in darker skin phototypes.Conclusions. Complete elimination of stretch marks remains unachievable; nonetheless, combination based, individualized approaches can significantly enhance their appearance. There is a critical need for robust, large scale randomized trials employing standardized, objective assessments, long term follow up, and inclusion of diverse skin phototypes and patient reported outcomes to establish evidence based treatment protocols.